Hydrogen isotopic fractionations during syntheses of lipid biomarkers in the seeds of broomcorn millet (Panicum miliaceum L.) under controlled environmental conditions. (April 2021) - Jacob, Jérémy; Bossard, Nicolas; Bariac, Thierry; Terwilliger, Valery; Biron, Philippe; Richard, Patricia; Le Milbeau, Claude; Vergès, Elisabeth
Highlights: Broomcorn millet was grown under controlled condition. H/D fractionation during seeds n -alkanes and miliacin synthesis was examined. Leaf water δ 2 H value is the primary driver of lipid δ 2 H values. Relative humidity could explain subtle differences in εbio between n -alkanes. Abstract: Compound specific hydrogen isotopic analyses have the potential to reveal the biosynthetic pathways of biomarkers and to reconstruct the effects of water stress in a plant, or in an ecosystem. Although C4 graminoids are of great geological interest and are some of the world's leading crops, there are few experimental studies of their biomarker responses to hydrological conditions. Here, we study a C4 graminoid, broomcorn millet, and compare the effects of controlled changes in environmental conditions on the distributions of n -alkane homologues and on the pentacyclic triterpene, miliacin, which is a biomarker for broomcorn millet; both were measured in the seeds of the graminoid. Broomcorn millet plants were propagated in hydroponic solutions with four different δ 2 H values for each of two growth chambers, differing in relative humidity (58 and 74%). Analyses of δ 2 H values of the lipid compounds (miliacin and n -alkanes) in seeds and water extracted from transpiring and non-transpiring organs allowed us to quantify the apparent (lipids vs. source water to plant) and biosynthetic (lipids vs. leaf water) fractionations during miliacin and n -alkane syntheses. Miliacin and n -alkane δ 2 H values were linearly related to leaf water δ 2 H values, permitting credible biosynthetic fractionations to be calculated for n -alkanes (average −149.5‰ ± 11) and miliacin (−118‰ ± 5). These biosynthetic fractionations were within the range of published values for compounds with their respective biosynthetic pathways, although a 2 H-enrichment of miliacin compared to n -alkanes remains unexplained. Whereas a 16% decrease in relative humidity had no significant impact on the biosynthetic fractionation of miliacin, n -C25 and n -C27 alkanes, it led to a 25‰ decrease in biosynthetic fractionation for n -C31 and n -C33 alkanes. This could be the consequence of a contribution of more depleted pools of hydrogen atoms in cytoplasmic water (compared to chloroplastic hydrogen pools) during the n -alkyl lipid elongation process. This finding suggests that the respective influences of source water δ 2 H values and relative humidity on the δ 2 H values of organic compounds may be discretely inferred by examining the δ 2 H values of compounds synthesized from distinct sources of hydrogen in cells. This provides clues to the biosynthetic fractionations in a C4 plant for compounds derived from distinct pathways, but also highlights specific issues related to seed lipids which require further research.